دور الثقافة التنظيمية في تحقيق الإبداع الإداري للمنظمة دراسة ميدانية على العاملين الإداريين في جامعة تشرين (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2017)
يهدف البحث إلى التعرف على مستوى الثقافة التنظيمية السائدة في جامعة تشرين, ومستوى الإبداع الإداري لدى العاملين الإداريين فيها, ودراسة العلاقة بين الثقافة التنظيمية السائدة وتحقيق الإبداع الإداري لدى العاملين الإداريين في الجامعة. اعتمد البحث المنهج الوصفي وشمل مجتمع البحث جميع العاملين الإداريين في جامعة تشرين والبالغ عددهم (1119) إدارياً, أما عينة البحث فقد تمّ تحديدها باستخدام قانون العينة الإحصائي وبلغت (286) إداري تمّ توزيع الاستبانة عليهم وأعيد منها (231) استبانة بنسبة استجابة بلغت (80.77%). وباعتماد الأساليب الإحصائية المناسبة كان من أهم النتائج التي تمّ التوصل إليها:*إنّ مستوى الثقافة التنظيمية السائدة في جامعة تشرين هو مستوى مرتفع وبأهمية نسبية (75.16%).*إنّ مستوى الإبداع الإداري لدى العاملين الإداريين في جامعة تشرين هو مستوى مرتفع فيما يتعلق بحل المشكلات واتخاذ القرار, والقابلية للتغيير, وتشجيع الإبداع.*تساهم الثقافة التنظيمية السائدة في جامعة تشرين في تحقيق الإبداع الإداري, حيث أنّ (67.2%) من التغيرات الحاصلة في تحقيق الإبداع الإداري تفسره الثقافة التنظيمية السائدة.The research aims to identify the level of organizational culture prevailing in Tishreen University, and the level of management innovation at the administrative staff, the study of the relationship between organizational culture and achieve the prevailing management innovation at the administrative staff at the university. Adopted Find descriptive approach and included the research community all administrative staff in Tishreen University's (1119) administratively, and the sample was determined using the statistical sample law amounted to (286) administrative distributed the questionnaire to them and returned them (231) the identification of, and response rate ( 80.77%). And the adoption of appropriate statistical methods was the most important results that have been reached:*The level of organizational culture prevailing in Tishreen University is the high level and the relative importance (75.16%).*The administrative creativity level of the administrative staff at Tishreen University is a high level with respect to problem-solving and decision-making, and the ability to change, and encourage creativity.*Contribute to organizational culture prevailing at Tishreen University in achieving administrative creativity, where (67.2%) of the developments in the achievement of administrative creativity interpreted by the prevailing organizational culture changes.